Ecological and economic assessment of the ecological situation transformation in the Republic of Kazakhstan regions in 1990–2020 - Bityukova, V.R. (Karagandy University of the name of acad. E.A. Buketov, 2022)
The article is devoted to problems of stating the complex index of anthropogenic impact (IAI) formation estimating the ecological stress level in regions of Kazakhstan. A system of indicators of anthropogenic stress for ecological monitoring is justified as different methods of normalization and aggregation of indices. Results of various estimations are provided. Factors of transformation of territorial structure of pollution are revealed. IAI shows that in the post-Soviet period, inherited ecological problems and new sources of impact determined the anthropogenic impact spatial shift at the regional level from the North and East to the South and West. Industry is losing its status as the main source of anthropogenic impact (AI), so densely populated areas and the increase in associated impact indicators have caught up with industry. The population outflow in Northern Kazakhstan has a positive effect on the AI level and increases AI in Southern Kazakhstan. The entire variety of scenarios for the dynamics of the impact of material production on the environment can be reduced to four types: ecological degradation, when an economic downturn is accompanied by increased environmental pollution; depressive development, when an economic downturn is accompanied by decreased pollution; extensive ecological development, where economic growth is accompanied by increased pollution; balanced development, when economic growth is accompanied by decreased pollution. During crisis years, there was a decrease in industrial pollution, the volume of atmospheric emissions and polluted wastewater, and, to a lesser extent, water consumption; conversely, vehicle emissions, the volume of toxic waste, the area of disturbed lands, and forest fires do not depend on the change in GRP. Despite the fact that for the country as a whole, the dependence of the level of pollution on the level and dynamics of economic development is weakening, with each new crisis, there is an increasing number of regions where the environmental state continues to deteriorate despite the economic downturn.
Keywords: ecological and economic analysis; pollution indicators; integral index ecological stress; ecological situation; anthropogenic impact; complex estimation